Condenser Damage Analysis using FTA And FMEA Methods at PLTU Nagan Raya - Arie Saputra; Sarijal Sarijal (LPPM Politeknik Aceh Selatan, 2022)
Based on observations made at the nagan raya power plant. The problem found in the condenser is damaged or blockaged in the condenser pipe which can interfere with the condensate water production process and the water used is seawater as a coolant to condense steam and then become condensate water after hammering the cooling process. Damage that occurs in the dominating scope of work occurs in a leaky or clogged condenser pipe. In this study, it used the FMEA method to find out the highest RPN value and the highest value determines the critical level of a component. Furthermore, the use of the FTA method is to analyze the causes of failures that have the potential to cause damage to the machine or tool. Based on the 5w + 1h table is what (what is the repair strategy ), why (why should be repaired), who (who did), where (where is the place of damage), when (when the repair was made), how (how the repair was carried out).The conclusion of data processing on the FMEA method was found to be the highest RPN value in leakage or clogging of condenser pipes by 150 and the lowest value of the lowest RPN in life time of 8. Meanwhile, the FTA method that has the potential to experience damage or the root of condenser damage is that there is sand in the cooling water and ball cleaning work that is not optimal and then results in clogging of the condenser pipe or can cause leaks in the condenser pipe. The purpose of this study is to identify the damage that occurs to the condenser to keep the level of damage or failure of condenser production from continuing. The final results of this study are expected to present the level of risk of condenser stability with the causative factors of each component of the failure.